RE-FIGURASI SOSIAL DALAM PRAKTIK PEMINJAMAN DANA BERBASIS TEKNOLOGI MEDIA DIGITAL: STUDI KASUS ATAS PLATFORM CICIL - Noviani, Ratna; Jesica, Elok Santi; Wardani, Rizki Cesira (Jurnal Masyarakat dan Budaya, 2023)
Cicil is a digital platform that offers loan lending services targeting higher education students in Indonesia. The practice of loan lending services by Cicil is generated by the web of interdependency between individuals, institutions, and ecosystem of digital platform. This study is aimed to examine social re-figuration, which molds the digital media technology-based practice of loan lending services by Cicil. By using Norbert Elias’ concept of figuration and Anthony Hepp’s adaptation of Norbert Elias’ figuration in the context of digital era as well as case study method, this study reveals the social transformation or social re-figuration in the practice of loan lending services in the digital era. The social re-figuration is characterized by the change of interdependent interactions among the involved social actors, which are increasingly mediatized. This study also shows that in the digital era participatory management and strategy of integration have replaced the hierarchical and non-cooperative management in the practice of loan lending services.